S-CODE: Switches and crossings optimal design and evaluation - Hába, Aleš; Kohout, Martin; Schmidová, Eva; Vágner, Jakub; Zelenka, Jaromír (University of Pardubice, 2018)
The S-CODE project is addressed all of the aims and objectives detailed in topic Research into new radical ways of changing trains between tracks – and work towards the developments required to realise Next Generation Switches and Crossings, as detailed in the Shift2Rail Multi-Annual Action Plan. The overall aim of the S-CODE project is to investigate, develop, validate and initially integrate radically new concepts for switches and crossings that have the potential to lead to increases in capacity, reliability and safety while reducing investment and operating costs. The project has identified radically different technology concepts that can be integrated together to achieve significantly improved performance for Switches and Crossings based around new operating concepts. Within this project the research team of University of Pardubice Faculty of Transport Engineering deals with optimisation of wheel-rail interface in Switches and Crossings and using of novel material for Switches and Crossings components. This paper contents particular results of both mentioned fields.
Keywords: paragraph; page; heading; footer